2011
DOI: 10.1371/journal.pone.0022162
|View full text |Cite
|
Sign up to set email alerts
|

Foraging Behavior under Starvation Conditions Is Altered via Photosynthesis by the Marine Gastropod, Elysia clarki

Abstract: It has been well documented that nutritional state can influence the foraging behavior of animals. However, photosynthetic animals, those capable of both heterotrophy and symbiotic photosynthesis, may have a delayed behavioral response due to their ability to photosynthesize. To test this hypothesis we subjected groups of the kleptoplastic sea slug, Elysia clarki, to a gradient of starvation treatments of 4, 8, and 12 weeks plus a satiated control. Compared to the control group, slugs starved 8 and 12 weeks di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…A number of other studies also reported the incorporation of 14 C from 14 CO 2 in plakobranchids that sequester plastids [30][31][32][33], but animals can also incorporate CO 2 via carboxylation reactions. The second line of evidence for plakobranchids being photosynthetic comes from the observation that once the plastids have been incorporated into the digestive gland, LtR species can survive for months in the absence of additional food [7,10,23,24,34,35]. Such plakobranchids are said to be 'starved' and are typically cultivated in the light [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…A number of other studies also reported the incorporation of 14 C from 14 CO 2 in plakobranchids that sequester plastids [30][31][32][33], but animals can also incorporate CO 2 via carboxylation reactions. The second line of evidence for plakobranchids being photosynthetic comes from the observation that once the plastids have been incorporated into the digestive gland, LtR species can survive for months in the absence of additional food [7,10,23,24,34,35]. Such plakobranchids are said to be 'starved' and are typically cultivated in the light [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Scale bar ϭ 20 m. san species with similar lengths of plastid function longevity as E. timida (2-4 mon; namely E. viridis, E. clarki) show a variety of specific adaptations in their cell biology to sustain the function of the algal organelle. In some cases, such as E. clarki, plastid maintenance mechanisms are sufficient to enable enough photosynthesis to occur for long enough to permit some independence from a food source (Middlebrooks et al, 2011(Middlebrooks et al, , 2012(Middlebrooks et al, , 2014. Although a few recent accounts based on E. timida have discounted the importance of photosynthetic function as well as the longevity and integration of symbiotic plastid function among the sacoglossans as a group (Wägele et al, 2011;Christa et al, 2013), it is clear that the broad differences in the adaptations among species makes generalizations based on one slug species unwarranted.…”
Section: Discussionmentioning
confidence: 99%
“…C. Transmission electron micrograph showing kleptoplasts within the cells of a digestive tubule cul‐de‐sac (from Middlebrooks et al. ). D. Elysia chlorotica (Type 4) from Menemsha, Massachusetts are even more uniformly green than E. clarki and cannot be anatomically shaded from exposure to sunlight (photo by P. Krug).…”
Section: Sacoglossan Kleptoplasty: Different Anatomy Among Slug Speciesmentioning
confidence: 99%
“…In these species, the chloroplasts merely photosynthesize until they burn out, using up whatever algal‐originated material was engulfed initially, so that chloroplasts must be replaced by continuous feeding by the slugs (reviewed in Middlebrooks et al. , ; Pierce & Curtis ; Curtis et al. ).…”
Section: Chloroplast Proteins Are Synthesized In the Host Cellsmentioning
confidence: 99%
See 1 more Smart Citation